The Influence of Financial Literacy, Lifestyle, and Digital Payments on the Financial Behavior of People in Kuningan Regency - Pemilia Mega Yuliani; Ario Purdianto (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the influence of Financial Literacy, Lifestyle, and Digital Payment Use on the Financial Behavior of the community in Kuningan Regency, both partially and simultaneously. The research method used is quantitative with an associative design. The population of this study is the people of Kuningan Regency who use digital payment services (such as e-wallets, mobile banking, or QRIS). The sampling technique used purposive sampling with a total of 150 respondents. Data were collected through a questionnaire based on a Likert scale of 1-5 and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results of the outer model test showed that all indicators had loading factor values ​​above 0.7 (ranging from 0.808 to 0.914), which means all instruments were declared valid and reliable. Partially, Financial Literacy has a positive effect on financial behavior, indicating that a good understanding of risk management and financial priorities will result in more rational financial decisions. Lifestyle and digital payment usage have also been shown to significantly influence people's financial behavior patterns. Simultaneously, these three independent variables significantly influenced financial behavior. This finding underscores the importance of strengthening financial literacy in the digital age to balance the ease of digital transactions with a consumerist lifestyle, leading to healthier and more stable financial management.